(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article focuses on the historical development of the Uzbek national cinema and theater in Europe in the early years of independence. After the independence of Uzbekistan, a new era of national cinema began. The development of relations in the field of cinema, the establishment of film exchanges between the countries played a key role in the demonstration of the creative products of large film companies. Over the years, Uzbek theater groups have gained international recognition by participating in festivals abroad with their programs. The events aimed at introducing our national art to the world have allowed for the establishment of cooperation between artists and professionals of different nations and laid the foundation for the exchange of cultures between peoples